Gender-Based Entrepreneurship Education as a Strategy for Inclusive and Sustainable Women's Creative Economy Development in Jember Regency - Noviana Mariatul Ulfa; Taufan Dwi Susilo; Arie Eko Cahyono (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to examine how gender-based entrepreneurship education (GBEE) can support the inclusive and sustainable development of women’s creative economy in Jember Regency, East Java. The study employed a qualitative phenomenological approach. Data were collected through in-depth interviews, focus group discussions, and document analysis involving 12 participants, including women entrepreneurs, educators, policymakers, and academics. The data were analyzed thematically through data immersion, open coding, category development, and theme construction. The findings identify four main themes: (1) persistent gender barriers in entrepreneurship education, including sociocultural restrictions, gender-insensitive curricula, and limited access to resources; (2) adaptive pedagogical strategies integrating situated learning, peer mentoring, and digital literacy; (3) the use of local creative economy sectors—such as batik, coffee agro-tourism, culinary arts, and fashion—as culturally relevant learning platforms; and (4) empowerment outcomes, including increased economic autonomy, stronger social capital, and improved negotiation capacity. The study concludes that GBEE not only strengthens women’s entrepreneurial skills but also contributes to shifts in household and community power relations. Collaboration among universities, government, and civil society is essential to implement gender-responsive entrepreneurship education aligned with SDG 5 and SDG 8.